Genetic variability, correlation and path analysis of floral, yield and its component traits in CMS and restorer lines of rice (Oryza sativa L.) - Bornare, SS; Mittra, SK; Mehta, AK (Bangladesh Journal of Botany, 2014)
The coefficients of phenotypic and genotypic variability were comparatively high for effective tillers/plant followed by grain yield/plant, plant height and angle of floret. High heritability accompanied with high genetic advance indicated predominance of additive gene action for the traits viz., 1,000 seed weight, plant height, anther breadth, anther length, effective tillers/plant and angle of floret opening. Selections can be effective on the basis of correlation and path analysis for characters like effective tillers/plant, spikelet density, angle of floret opening, duration of floret opening, panicle length, 1,000 seed weight and days to 50 per cent flowering. With respect to findings of the investigation, CMS lines viz., APMS 6A, IR 69622A, IR 62829A, IR 70369A and IR 68886A were identified as superior female lines with respect to floral, yield and its contributing traits whereas, among the restorer lines NPT-10, NPT-13-01, R-710 and Sugandh-3 were identified as putative lines. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19745 Bangladesh J. Bot. 43(1): 45-52, 2014 (June)